Pendidikan Jiwa dalam Perspektif Ibnu Qayyim al-Jauziyyah - Muarifah, Muarifah; Rokhimah, Siti (Lembaga Yasin AlSys, 2026)
The concept of soul education (tarbiyah al-nafs) in the thought of Ibn Qayyim al-Jauziyyah has important relevance for the development of contemporary Islamic education, particularly in responding to the moral and spiritual crises within modern educational contexts. This article aimed to examine in depth Ibn Qayyim’s concept of soul education by focusing on its theoretical foundations, educational aims, methodological framework, and implications for Islamic education. The study employed a qualitative approach through a library study by analyzing Ibn Qayyim’s major works, including Madarij al-Salikin, Ighathat al-Lahfan, Zad al-Ma‘ad, and Tuhfat al-Mawdud, as well as relevant secondary sources. The findings show that Ibn Qayyim viewed the soul as a dynamic entity that can be educated and requires an ongoing process of purification, self-regulation, and continuous cultivation through faith education, moral habituation, and spiritual practice. Soul education aims to form individuals with purified hearts, upright moral character, and awareness of their spiritual and social responsibilities. These findings affirm that Ibn Qayyim’s thought offers a holistic and integral educational approach that is relevant for addressing moral and spiritual crises in modern education, while providing a conceptual contribution to strengthening a contemporary Islamic education paradigm oriented toward character formation.